ANALISIS EXISTING DAN FORECASTING PUSKESMAS BLUD KOTA PEKALONGAN : UPAYA MENUJU KEMANDIRIAN PENGELOLAAN LAYANAN KESEHATAN PRIMER - Irawan, Teguh; Latif, Rr. Vita Nur; Wahyuningsih, Wahyuningsih (JURNAL LITBANG KOTA PEKALONGAN, 2016)
CURRENT CONDITION ASSESSMENT AND ANALYSIS OF THE SUSTAINABILITY OF HEALTH CENTERS BLUDS IS IMPORTANT THAT REQUIRE FURTHER STUDY IN ORDER TO FORMULATE STRATEGIES FOR STRENGTHENING THE IMPLEMENTATION OF A BREAKTHROUGH IN PEKALONGAN CITY BLUDS HEALTH CENTERS. THIS STUDY AIMS TO ANALYZE EXISTING AND FORECASTING HEALTH CENTERS BLUDS PEKALONGAN CITY: EFFORTS TOWARDS INDEPENDENCE IN THE MANAGEMENT OF PRIMARY HEALTH CARE. THESE STUDIES INCLUDED EXPLORATORY RESEARCH STUDY WITH QUALITATIVE APPROACH THAT IS SUPPORTED BY STATISTICAL DATA TO TRIANGULATE THE SOURCETHROUGH IN-DEPTH INTERVIEW ON THE MAIN INFORMANT (8 HEADS OF HEALTH CENTERS), INFORMANTS TRIANGULATION (2 MANAGERS AND 2 BLUDS HEALTH DEPARTMENT) AND COMPANION INFORMANTS (16 VISITORS OF HEALTH CENTER). USING RESEARCH INSTRUMENTS INTERVIEWING GUIDANCE. METHODS OF DATA COLLECTION USING IN-DEPTH INTERVIEW WITH TRIANGULATION. DATA PROCESSED BY DATA REDUCTION APPROACHES, TESTING THE PROPOSITION, AND THE WITHDRAWAL OF THE MAJOR CONCLUSIONS. INPUT INDICATORS EXSISTING ANALYSIS RESULTS ON A MAP TBSP COMPLIANCE HAS BEEN MET WITH A PROPORTION OF 70% ENERGY AND 30% CIVIL SERVANTS AND QUALIFIED EMPLOYEES BLUDS ALREADY MEETS 6 PROFESSIONAL HEALTH WORKERS. BUT SOME CONDITIONS STILL REQUIRE THE APPLICATION OF DOUBLE DUTY. CENTRALIZED RECRUITMENT PATTERNS MADE BY MANAGER SKILL DEVELOPMENT BLUDS ACCOMPANIED BY TRAINING ALTHOUGH FOR THE DEVELOPMENT OF CIVIL SERVANTS STILL POWER TAKE PRECEDENCE. ON ASPECTS OF FINANCIAL GOVERNANCE HAS FOCUSED ON THE MANAGEMENT SYSTEM BLUDS HAS SOME ADVANTAGES AND DISADVANTAGES. THE LOGISTIC ASPECTS OF HEALTH CENTERS, IMPLEMENTED BY THE MANAGEMENT HOLDING BLUDS PEKALONGAN CITY HEALTH CENTERS. ASPECTS OF THE PROCESS INCLUDING: PLANNING, ORGANIZING, AND EVALUATION GENERALLY NOT MUCH DIFFERENT FROM BEFORE BLUDS, AS A POINT OF EMPHASIS BLUD’S MORE TO FINANCIAL GOVERNANCE, IS NOT AT VARIANCE SERVICE PROGRAM. FORCASTING ANALYTICAL RESULTS REFER TO THE DEVELOPMENT OF STRATEGIES TO CONTINUE HOLDING TWO APPROACHES, WITH SOME IMPROVEMENTS AND TRANSFORMATION OF THE PATTERN OF THE CONCEPT OF SELF BLUDS. SELF-CONCEPT DEVELOPMENT PATTERN THAT IS A "PILOT PROJECT" THROUGH SEVERAL STAGES AIMED AT IMPROVING PRIMARY HEALTH CARE.